Climate refugees [videorecording (DVD)] - Begley, Ed, Jr; Nash, Michael P.; Obama, Barack; Gore, Al, 1948-; Gingrich, Newt (Multicom Entertainment, 2018)
This film documentary elucidates what happens when an overpopulated world and a changing climate collide, displacing people and forcing mass migration.